Oceanographic Data of the 28th Japanese Antarctic Research Expedition from November 1986 to April 1987 - ミチダ, ユタカ; イナズミ, シノブ; MICHIDA, Yutaka; INAZUMI, Shinobu (National Institute of Polar Research, 1988)
P(論文) The results of the oceanographic observations on board icebreaker Shirase and tidal observation at Syowa Station are presented in this report. The oceanographic observations were carried out in the summer mission of the 28th Japanese Antarctic Research Expedition (JARE-28) in 1986-1987. Tidal observation was continued through the winter mission of JARE-27 in 1985-1986. departmental bulletin paper